GABAergic contribution to the muscle mechanoreflex-mediated heart rate responses at the onset of exercise in humans - Teixeira, André L.; Ramos, Plinio S.; Samora, Milena; Sabino-Carvalho, Jeann L.; Ricardo, Djalma R.; Colombari, Eduardo [UNESP]; Vianna, Lauro C. (American Physiological Society, 2018)
Previous studies have indicated that central GABAergic mechanisms are involved in the heart rate (HR) responses at the onset of exercise. On the basis of previous research that showed similar increases in HR during passive and active cycling, we reasoned that the GABAergic mechanisms involved in the HR responses at the exercise onset are primarily mediated by muscle mechanoreceptor afferents. Therefore, in this study, we sought to determine whether central GABA mechanisms are involved in the muscle mechanoreflex-mediated HR responses at the onset of exercise in humans. Twenty-eight healthy subjects (14 men and 14 women) aged between 18 and 35 yr randomly performed three bouts of 5-s passive and active cycling under placebo and after oral administration of diazepam (10 mg), a benzodiazepine that produces an enhancement in GABAA activity. Beat-to-beat HR (electrocardiography) and arterial blood pressure (finger photopletysmography) were continuously measured. Electromyography of the vastus lateralis was obtained to confirm no electrical activity during passive trials. HR increased from rest under placebo and further increased after administration of diazepam in both passive (change: 12 ± 1 vs. 17 ± 1 beats/min, P < 0.01) and active (change: 14 ± 1 vs. 18 ± 1 beats/min, P < 0.01) cycling. Arterial blood pressure increased from rest similarly during all conditions (P > 0.05). Importantly, no sex-related differences were found in any variables during experiments. These findings demonstrate, for the first time, that the GABAergic mechanisms significantly contribute to the muscle mechanoreflex-mediated HR responses at the onset of exercise in humans. NEW & NOTEWORTHY We found that passive and voluntary cycling evokes similar increases in heart rate and that these responses were enhanced after diazepam administration, a benzodiazepine that enhances GABAA activity. These findings suggest that the GABAergic system may contribute to the muscle mechanoreflex-mediated vagal withdrawal at the onset of exercise in humans.
Keywords: Autonomic nervous system; Benzodiazepines; Vagal withdrawal